2012
DOI: 10.3758/s13421-012-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the advantage of the upper part of words occur at the lexical level?

Abstract: Several recent studies have shown that the upper part of words is more important than the lower part in visual word recognition. Here, we examine whether or not this advantage arises at the lexical or at the letter (letter feature) level. To examine this issue, we conducted two lexical decision experiments in which words/pseudowords were preceded by a very brief (50-ms) presentation of their upper or lower parts (e.g.,). If the advantage for the upper part of words arises at the letter (letter feature) level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
(38 reference statements)
5
10
0
Order By: Relevance
“…Finally, it is important to note that, despite its potential ambiguity, the lower parts of upwardunbalanced words can produce some lexical activation/ interference (a 38-ms lexical interference). This is consistent with the presence of reliable masked-priming effects with the lower parts of words that have been reported in previous research (i.e., can still produce some activation on the word molino ["mill"]; see Perea et al 2012a;Perea et al 2012b, for additional evidence with briefly presented foveal previews). It also reveals that the cognitive system can readily normalize partial information during lexical access (see, e.g., Jordan et al, 1999;Perea, Duñabeitia, & Carreiras, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, it is important to note that, despite its potential ambiguity, the lower parts of upwardunbalanced words can produce some lexical activation/ interference (a 38-ms lexical interference). This is consistent with the presence of reliable masked-priming effects with the lower parts of words that have been reported in previous research (i.e., can still produce some activation on the word molino ["mill"]; see Perea et al 2012a;Perea et al 2012b, for additional evidence with briefly presented foveal previews). It also reveals that the cognitive system can readily normalize partial information during lexical access (see, e.g., Jordan et al, 1999;Perea, Duñabeitia, & Carreiras, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…The simplest explanation of the present data is that the apparent bias for the upper part of words reported in previous experiments-from the simple demonstrations by Huey (1908) or Chou (1930) to recent experiments that have employed various techniques (e.g., Blais et al, 2009;Perea, 2012;Perea et al 2012a;Perea et al 2012b;Shimron & Navon, 1980;Tsao & Wang, 1983)-can be attributed to the fact that these languages simply include more upwardunbalanced words than balanced or downward-unbalanced words (i.e., English, Spanish, Portuguese, French, or Chinese). Indeed, when the words of a given language contain more downward-unbalanced words than upward-unbalanced words, as is the case with Hebrew, the lower part of words has an advantage when reading a text.…”
Section: Discussionmentioning
confidence: 80%
“…Bold emphasis influences the speed of lexical access in normal viewing conditions (i.e., in absence of visual noise). Importantly, the interaction between word-frequency and bold emphasis reflects that even though the effect of bold emphasis may initially occur at an early letter encoding stage, its impact carries over further down the word processing stream: it affects to a larger degree low-frequency than high-frequency words (e.g., see Perea & Rosa, 2002; Perea et al, 2012, for a similar pattern with other perceptual factors). It is important to note here that the effect of bold emphasis did not affect the response times for the pseudowords.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, it is important to note that the effect of bold emphasis may carry over further down along the word-processing stream, so that it may affect frequent and infrequent words in a different way. In this light, Perea and Rosa (2002) reported that low-frequency words were responded to faster when presented in lowercase than when presented in UPPERCASE, while there were no signs of a lowercase/UPPERCASE difference with high-frequency words (see also Perea, Comesaña, & Soares, 2012, for a parallel finding). Perea and Rosa (2002) argued that familiar words accelerate toward resonance (i.e., perceptual identification) quickly in a resonance model (see Van Orden & Goldinger, 1994), and hence they would be less affected by the format of bottom-up information than unfamiliar words.…”
mentioning
confidence: 94%
“…In our study, we conducted two lexical decision experiments using a delayed segment technique with lowercase stimuli. In this technique, a partial preview appears for 50 ms and is immediately followed by the whole target item (Perea, Comesaña, & Soares, 2012; see also Carreiras, Gillon-Dowens, Vergara, & Perea, 2008;Lee, Rayner, & Pollatsek, 2001, for previous experiments with this technique). Compared with the paradigms employed in previous experiments, this constitutes a closer situation to the actual process of lexical access in normal reading because letters were presented in lowercase, embedded in words, and remained unaltered (i.e., non-degraded) except for the initial 50 ms of exposure.…”
Section: The Delayed Segment Techniquementioning
confidence: 99%